1. Divine Liturgy in the Vision of Narsai 2. Jesus Christ the Saviour: Soteriology According to East Syriac Tradition 3. Critical Ontology: An Introductory Essay - Chethimattam, John B. (Journal of Dharma, 2003)
1. Francis Kanichikattil, Divine Liturgy in the Vision of Narsai, Bangalore: Dharmaram Publications, 2003, pages 126, ISBN:81-86861-49-1. 2. Thomas Anikuzhikattil, Jesus Christ the Saviour: Soteriology According to East Syriac Tradition, Satna: Ephrem Publications, 2002, pages ix + 392, ISBN: 81-88065-01-3. 3. Joseph Kaipayil,. Critical Ontology: An Introductory Essay, Bangalore: Jeevalaya Institute of Philosophy, 2002, pages x + 55, ISBN: 81-87664-02-9.